Total Plasma Homocysteine Concentrations in Puerto Rican Patients With Presumptive Atherosclerotic Coronary Disease - Rodríguez, José F.; Rodríguez, Jorge L.; Escobales, Nelson; Cruz, Damaris; Banch, Héctor; Rivera, Cynthia; Altieri, Pablo I. (Puerto Rico Health Sciences Journal, 2013)
See manuscript